2013
DOI: 10.2147/ijwh.s47604
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to use of modern contraceptives among women in an inner city area of Osogbo metropolis, Osun State, Nigeria

Abstract: ObjectivesTo determine the knowledge and attitudes on modern contraceptive use of women living in an inner city area of Osogbo.Materials and methodsThree hundred and fifty nine women of childbearing age were studied utilizing a community-based, descriptive, cross-sectional study design. A multistage random sampling technique was used in recruiting respondents to the study. A four-part questionnaire was applied dually, by interviewers and by respondents’ self administration, and the data was analyzed using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
87
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(113 citation statements)
references
References 19 publications
(19 reference statements)
19
87
2
Order By: Relevance
“…This is the literature trend that high contraceptive knowledge does not always result in a corresponding high contraceptive use 6,17,18 .…”
Section: Prevalence Of Contraceptive Usementioning
confidence: 80%
See 2 more Smart Citations
“…This is the literature trend that high contraceptive knowledge does not always result in a corresponding high contraceptive use 6,17,18 .…”
Section: Prevalence Of Contraceptive Usementioning
confidence: 80%
“…Significant among the many reasons are socio-cultural and religious beliefs, shallow understanding concerning pregnancy and contraception, scarcity of products, aggressive attitudes of health providers toward adolescents who desire contraception services, ignorance and misinformation 6,17,23 . A global study revealed that 56% of young married women are intentionally pregnant (so do not use contraceptives); 20% are using contraception, and 24% are not desirous of being pregnant but still refuse to use contraceptives.…”
Section: Prevalence Of Contraceptive Usementioning
confidence: 99%
See 1 more Smart Citation
“…This evidence is far-reaching of the potential benefits of women educational status on contraceptive and maternity seeking behavior in developing countries 7,24,42,43 . By responding to noneducated women concerns through focused counselling, contraceptive misconceptions, myths and cultural norms that divest women's intention for use could be addressed.…”
Section: Addressing Women Ever and Current Contraceptive Use Concernsmentioning
confidence: 89%
“…These barriers affecting women's choices for fertility needs are described as -remarkably pervasive‖ 6 . Barriers affecting women's choices are also increasingly evidenced to affect women's ability to effectively regulate their reproductive choices in the short to long term [6][7][8] . Unintended pregnancies resulting from unplanned pregnancies are the consequences of poor contraceptive use in most developing countries 9 .…”
Section: Introductionmentioning
confidence: 99%